Banks and FinTech Relationship in a Digital Transformation Context - Jihane, Tayazime; Aziz, Moutahaddib (European Scientific Journal, ESJ, 2022)
The main function of digitalization is to make relationships more flexible and less framing, while allowing simpler and faster communication and more important data exchange. The digitalization of the banking sector is reforming it in its most profound axes. Its functioning, its organization, its interactions, its products, all have been modified, including back-office functions. The digital infrastructure has accelerated the emergence of new technologies: social media, cloud computing, analytics and big data, wearable devices, etc. This new technological wave has led to the emergence of new entrants in the financial sector. Financial technology, also known as FinTech, is an industry composed of diversified firms that combine financial services with innovation technologies offered to financial service providers (MoroVisconti, R. et al, 2020). Banks will have to engage in further cost-cutting since they remain shockingly costly, which partly explains the market penetration by FinTechs (Philippon, 2016). They offer unbundled low-cost services which makes them very competitive with banks. Therefore, the relationship between the two may be quite competitive because of the similar operations. In this article we will be discussing the nature of banks and FinTechs’ relationship, starting with a literature review and then a survey discussing these two financial structures.